ANALISIS PERBANDINGAN KINERJA KEUANGAN BANK SYARIAH DENGAN BANK KONVENSIONAL - Harri Yuni Rachman; Lela Nurlaela Wati; Refren Riadi (STIE Muhammadiyah Jakarta, 2020)
This research aims to determine the level of readiness of national banks, especially Sharia Commercial Banks in facing business competition in 2023 in terms of the company's financial performance aspects. The sample in this study was three (3) commercial banks three (3) Syaria Bank for the period 2014 - 2018. The analytical tool used to prove the hypothesis in this study is the independent sample t-test. The information used to measure bank financial performance is based on Bank Financial Publication Reports for the period 2014 - 2018 using CAMEL (Capital, Asset, Management, Earning, and Liquidity) financial valuation indicators summarized in CAR, BOPO, LDR, NIM financial ratios, ROA and NPL. The result of this study showed that there were significant differences, especially the BOPO, ROA and NPL indicators. As for the CAR, LDR and NIM indicators, there was no significant difference. However, when viewed from all aspects of indicators, Islamic Commercial Banks have not been able to show better financial performance compared to Conventional Commercial Banks